Evaluating Teachers' Learning, Perceptions, and Cultural Differences Following Professional Development for Early Literacy Software - Constanza Uribe-Banda (The Canadian Network for Innovation in Education (CNIE), 2021)
The present study examined the impact of professional development training on Canadian and Kenyan teachers’ confidence, comfort, and perceptions of their abilities to teach early literacy skills in the primary or elementary grades. Data were collected prior to and following training on how to integrate early literacy software as part of ongoing in-class instruction. Domain and technology constructs consistent with Mishra and Koehler’s (2006) technology integration model were assessed, as were perceptions related to delivery pacing. Overall, outcomes reflected more similarities than differences across the two groups of teachers. Limitations in foundational knowledge regarding concepts specific to early literacy were evident in both groups, despite higher levels of perceived confidence in Kenyan teachers compared to Canadian teachers in some content areas. Perceived comfort using technology and teaching with technology were highly correlated, with no differences observed across teacher groups. Pacing was perceived to be faster for Kenyan teachers compared to Canadian teachers. Implications for professional development in this domain are discussed.